2011
DOI: 10.1111/j.1467-8381.2011.02055.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Trade Balances: Evidence from Malaysia*

Abstract: This study examines the impacts of real exchange rates on the bilateral trade balances of Malaysia with the USA, Japan and Singapore. The results for the long‐run cointegrating vectors show that depreciation or devaluation of real exchange rates will improve bilateral trade balances. In the short run, there is some evidence of the J‐curve phenomenon. Changes in real money supply contribute greatly to changes in real exchange rates. Generally, changes in real exchange rates contribute significantly to changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…They also did not find J-curve relation. Tsen (2011) examined the impacts of real exchange rates on the bilateral trade balances of Malaysia with the USA, Japan and Singapore. The results showed that depreciation of real exchange rates improves bilateral trade balances in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They also did not find J-curve relation. Tsen (2011) examined the impacts of real exchange rates on the bilateral trade balances of Malaysia with the USA, Japan and Singapore. The results showed that depreciation of real exchange rates improves bilateral trade balances in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An understanding of the study on the impact of exchange rates on trade balance helps governments to improve trade balances with other countries (Tsen, 2011). Financial crisis is imminent when a country experiences a persistent trade balance deficit.…”
Section: Understanding the Effect Of Exchange Rate On Trade Balancementioning
confidence: 99%
“…Dapatan kajian Bahmani-Oskooee dan Fariditavana (2015) telah disokong banyak pengkaji selepasnya seperti Baek dan Choi (2020), Bahmani-Oskooee dan Baek (2019), Bahmani-Oskooee dan Harvey (2017) dan Bahmani-Oskooee dan Saha (2017). Bagi mengkaji kewujudan keluk-J di Malaysia, beberapa kajian telah dijalankan antaranya Sahlan et al, (2008), Yusoff (2009), Tsen (2011), Chan dan Hooy (2012), Rahim dan Shahwahid (2014) dan Ali et al (2014). Namun demikian, kajian-kajian ini lebih menumpukan kepada perdagangan agregat dan kesan simetrik.…”
Section: Teori Dan Sorotan Kajian Lepasunclassified